The Genus Sintula (Aranei, Linyphiidae) in Ukraine, with the Description of a New Species - Gnelitsa, V.A. (Вестник зоологии, 2012)
The data on biology of three species of the genus Sintula Simon, 1884 with their distribution in Ukraine are presented. Sintula solitarius Gnelitsa, sp. n. from the Crimean Peninsula is described. The genitalia of all four species are depicted.